A Phenomenological Investigation of the Unmet Needs of Newcomers Experiencing Insecure Housing in the Waterloo Region - Abbey Davis; Paula Fletcher (International Journal on Homelessness)
Insecure housing, like other categories of homelessness, leads to a plethora of unmet needs, yet remains hidden. Newcomers arriving in Canada within the last 10 years are particularly vulnerable to experiencing homelessness but are understudied. The purpose of this study was to investigate the unmet needs of newcomers experiencing insecure housing in the Waterloo Region, Canada. Using interpretive phenomenology, semi-structured interviews were conducted with 10 participants. Interviews revealed unmet health needs related to food insecurity and lack of health insurance coverage, including meal avoidance, compromised food quality, medical noncompliance, and costly health service avoidance. Unmet employment needs emerged due to frequent unemployment and underemployment despite high levels of education. The settlement process directly contributed to unmet employment needs for newcomers that were not international students by restricting employment with long wait time for work permits. Without work permits, newcomers were forced to accept inadequate funds from Ontario Works. While well-intentioned, community and government supports could not adequately support newcomers in insecure housing situations due to limited knowledge of newcomers, lack of guidance during the settlement process, and broken connections between community service agencies. Recommendations include improving the timeliness of work permits, increasing the funding from Ontario Works, amending Ontario Health Insurance Plan to cover health costs for newcomers waiting for work permits, wrap-around services for newcomers in the Waterloo Region, and interventions in post-secondary institutions to address food insecurity and inadequate health insurance coverage for international students.